Vpliv razmer pri razprševanju taline na lastnosti jeklenega granulata - Zupanič, Franc (Kovine zlitine tehnologije, 1999)
In this investigation we studied the influence of processing parameters by melt atomisation on the properties of a high carbon steel shot. We performed atomisation of nine heats in industrial conditions (Abrasiv Muta) by known processing parameters such as temperature and flow rate of the melt, temperature and pressure of the atomising water, temperature and level of water in the cooling pool... It has been found out that the pressure of the atomising water determines in a great extend the size distribution, spheroidity and wear resistance of the cast steel shot, although the influence of other parameters is not negligible. Results also suggest that larger granulation contains more defects than smaller, with consequentional detrimental effects on their wear resistance.
Keywords: jeklo; talina; razprševanje; granulat; vplivi